Welfare and excess volatility of exchange rates - Matteo Salto; Tito Pietra (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We study the properties of a GEI model with nominal assets, outside money (injected into the economy as in Magill and Quinzii), and multiple currencies. We analyze the existence of monetary equilibria and the structure of the equilibrium set under two different assumptions on the determination of the exchange rates. If currencies are perfect substitutes, equilibrium allocations are indeterminate and, generically, sunspot equilibria exist. Generically, given a nonsunspot equilibrium, there are Pareto improving (and Pareto worsening) sunspot equilibria associated with an increase in the volatility of the future exchange rates. We interpret this property as showing that, in general, there is no clear-cut effect on welfare of the excess volatility of exchange rates, even when due to purely extrinsic phenomena.
Keywords: D52; 330